GENETIC VARIATION IN TWO PHENOTYPES OF BALI CATTLE (Bos javanicus) INFERRED BY (AG)9C ISSR MARKER - Widya Pintaka Bayu Putra; Endang Tri Margawati; Ahmad Furqon; I Ketut Puja; Hasbi Hasbi (Tropical and Subtropical Agroecosystems)
Background. Bali cattle (Bos javanicus) are Indonesian native cattle that are kept as beef cattle. Among Bali cattle, however, there are white Bali cattle, called Taro cattle which are found in small numbers of the population and used only for religious ceremony needs. Objective. To quantify the genetic variation in two phenotypes of Bali cattle (wildtype and white colors) with inter-simple sequence repeat (ISSR) primer of (AG)9C. Methodology. Forty Bali cattle, 20 wildtype bulls, and 20 white Bali cows were used. The blood samples were taken from the jugular vein of each animal using venoject vacutainer tube containing EDTA. The DNA extraction was performed using DNA extraction kit following the manufacturer’s protocol. Number of DNA fragments, number of effective alleles (ne), and polymorphic informative content (PIC) were calculated to describe the genetic diversity in animals under study. Results: Results showed that three haplotype (H) types were observed in the animals under this study based on the ISSR fragments. The polymorphic informative content (PIC) in the white animals was higher than in the wild-type animals (0.62 vs 0.18). According to (AG)9C ISSR marker, mostly white (50%) and wildtype (90%) animals were classified into H2 type. Therefore, a total of 25% of white and 10% of wild-type animals were classified into H3 type. While 25% of white animals were classified into H1 type. Implications. the information generated in this study can be used as early information to investigate the molecular genetics of Taro cattle. Conclusions: This study suggests that many white animals have a specific locus which is absent in wild-type animals.